Astro City Metrobook - Busiek, Kurt 1960- (Image Comics, 2022)
"A hero dreams of flight. An alien spy prepares for invasion. A young man is mentored by a hero with dark secrets. A street criminal discovers a hero's identity. And much, much more. Step into a world of heroes and see them from a whole different perspective. These are the multiple-award-winning stories that began the epic series and changed how we think about superheroes"--Amazon.com